2004
DOI: 10.1002/jccs.200400146
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Synthesis of Some Pyrazolinone and Pyrazole Derivatives

Abstract: A convenient synthesis of some novel 6‐amino‐4‐aryl‐1‐phenyl‐3‐pyridin‐4‐yl‐1,4‐dihydropyrano[2,3‐c]pyrazole‐5‐carbonitriles (3a,b) and 5‐chloro‐1‐phenyl‐3‐pyridin‐4‐yl‐1H‐pyrazole‐4‐carbaldehyde (4) is described. Compound 4 was obtained by the reaction of 2‐phenyl‐5‐pyridin‐4‐yl‐2,4‐dihydropyrazol‐3‐one (1) with dimethylformamide and phosphorus oxychloride under Vilsmeier‐Haack reaction conditions. Compound 4 was subjected to react with different reagents such as hippuric acid, sodium azide and aromatic keton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…For compounds 15 and 16 bearing ortho-and para-Cl phenyl substituents, respectively, at the N-1 position, the induction effect of the N-1 para-Cl substituent was stronger than ortho-Cl (77% vs. 72%, Table 2). All 6-[(formyloxy)methyl]-1H-pyrazolo [3,4-d]pyrimidines (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) were characterized by spectroscopic methods. The structure of 6-[(formyloxy)methyl]-1H-pyrazolo [3,4-d]pyrimidine 24 was also characterized by X-ray crystallography and the ORTEP drawing is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For compounds 15 and 16 bearing ortho-and para-Cl phenyl substituents, respectively, at the N-1 position, the induction effect of the N-1 para-Cl substituent was stronger than ortho-Cl (77% vs. 72%, Table 2). All 6-[(formyloxy)methyl]-1H-pyrazolo [3,4-d]pyrimidines (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) were characterized by spectroscopic methods. The structure of 6-[(formyloxy)methyl]-1H-pyrazolo [3,4-d]pyrimidine 24 was also characterized by X-ray crystallography and the ORTEP drawing is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pyrazolopyrimidines can also be accessed via heterocyclization using starting materials such as 5-amino-4formypyrazoles, 22 5-amino-1H-4-pyrazolcarbonitriles, 23 and 5amino-1H-4-pyrazolcarboxamides. [23][24][25][26] However, the method for preparing pyrazolopyrimidines involves harsh conditions, long reaction times, complex synthetic procedures, and tedious purication steps. 27 Therefore, convenient synthetic routes for the synthesis of pyrimidine fused heterocyclic systems have attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…The initial precursors (2-4) were prepared with reported protocols and compared with the literature data. [45][46][47][48] General Procedure for the synthesis of bispyrazolyl-1,3,4oxadiazoles 5 (a-f)…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of pyrrolo [2,3-c]pyrazole derivatives 3a and 3b. 55 reported that treatment of 5-azido-1-phenyl-3-pyridin-4-yl-1H-pyrazole-4-carbaldehyde 6 with hydrazine hydrate 7 in the presence of acetic acid in ethanol at reflux yielded 1-phenyl-3-pyridin-4-yl-1,6-dihydropyrazolo [3,4-c]pyrazole 8. On the other hand, treatment of 7 with hydrazine hydrate 7 at room temperature in the presence of iodine afforded 6-phenyl-4-pyridin-4-yl-6H-pyrazolo [3,4-c]pyrazol-2-ylamine 9 (Scheme 3).…”
Section: Introductionmentioning
confidence: 99%